Unraveling the interplay of kinesin-1, tau, and microtubules in neurodegeneration associated with Alzheimer’s disease - Durairajan, Siva Sundara Kumar; Selvarasu, Karthikeyan; Singh, Abhay Kumar; Patnaik, Supriti; Iyaswamy, Ashok; Jaiswal, Yogini; Williams, Leonard L.; Huang, Jian-Dong (Frontiers in Cellular Neuroscience, 2024)
Alzheimer's disease (AD) is marked by the gradual and age-related deterioration of nerve cells in the central nervous system. The histopathological features observed in the brain affected by AD are the aberrant buildup of extracellular and intracellular amyloid-β and the formation of neurofibrillary tangles consisting of hyperphosphorylated tau protein.Axonal transport is a fundamental process for cargo movement along axons and relies on molecular motors like kinesins and dyneins. Kinesin's responsibility for transporting crucial cargo within neurons implicates its dysfunction in the impaired axonal transport observed in AD. Impaired axonal transport and dysfunction of molecular motor proteins, along with dysregulated signalling pathways, contribute significantly to synaptic impairment and cognitive decline in AD. Dysregulation in tau, a microtubule-associated protein, emerges as a central player, destabilizing microtubules and disrupting the transport of kinesin-1. Kinesin-1 superfamily members, including kinesin family members 5A, 5B, and 5C, and the kinesin light chain, are intricately linked to AD pathology. However, inconsistencies in the abundance of kinesin family members in AD patients underline the necessity for further exploration into the mechanistic impact of these motor proteins on neurodegeneration and axonal transport disruptions across a spectrum of neurological conditions. This review underscores the significance of kinesin-1's anterograde transport in AD. It emphasizes the need for investigations into the underlying mechanisms of the impact of motor protein across various neurological conditions. Despite current limitations in scientific literature, our study advocates for targeting kinesin and autophagy dysfunctions as promising avenues for novel therapeutic interventions and diagnostics in AD.